2010
DOI: 10.1038/ki.2010.253
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of memory-relevant brain regions during a dialysis cycle

Abstract: Cognitive impairment is a common and largely undiagnosed finding in a significant number of dialysis patients. These alterations may result from concomitant cerebrovascular disease, hemodynamic instability, the uremic milieu, or changes induced by the dialysis process. In order to gain further insight into this, we recruited 12 stable chronic hemodialysis patients (without clinical neurological disease) and an age- and gender-matched cohort of 12 control individuals (without renal or neurological problems) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
(48 reference statements)
0
27
0
1
Order By: Relevance
“…These changes were more prominent in haemodialysis patients compared to non-dialysed end-stage kidney disease patients and correlated with CI, pre-dialysis serum creatinine and duration of haemodialysis [45-46]. Another functional MRI study of the whole brain in haemodialysis patients showed bilateral activation of hippocampus suggesting activation of memory-relevant brain areas during dialysis [47]. These conclusions suggest that the haemodialysis process may have a role in CI.…”
Section: Discussionmentioning
confidence: 92%
“…These changes were more prominent in haemodialysis patients compared to non-dialysed end-stage kidney disease patients and correlated with CI, pre-dialysis serum creatinine and duration of haemodialysis [45-46]. Another functional MRI study of the whole brain in haemodialysis patients showed bilateral activation of hippocampus suggesting activation of memory-relevant brain areas during dialysis [47]. These conclusions suggest that the haemodialysis process may have a role in CI.…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study indicated that cognitive impairment is reversible by HD and increasing the HD frequency could induce beneficial effects on patients' cognitive function [68]. In the literature, there is an agreement that HD therapy improves cognitive function in CKD patients [69,70]. Although, it is well known that cognitive function is believed to be best 24 hours after the HD session, the variation of cognitive function during the HD circle has not been investigated yet.…”
Section: Impact Of Inflammation In Cognitive Impairment In Ckd Patientsmentioning
confidence: 91%
“…There were 46 studies meeting the inclusion criteria for final analysis [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55]. An overview of the reviewed articles is presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%